Astaxanthin â€“ King of antioxidants as immune modulator and anti-inflammatory for enhancing productive performance and health of animals - Singh, S V; Somagond, Yallappa M; Somagond, Yallappa M; Deshpande, Aditya; Deshpande, Aditya (Indian Journal of Dairy Science, 2021)
Astaxanthin is the potent antioxidant predominantly found in living organisms that are present in marine environment. It is known as â€œKing of antioxidantâ€ or â€œSuper vitamin Eâ€ because of its potent antioxidant property. Antioxidant property of astaxanthin known to modulate different biological activity relating to antioxidant defence system, inflammation, immunity and ameliorating adverse effect of oxidative stress during summer season. Its use has been found in improving both male and female reproductive health and production performance of bovines. Astaxanthin helps in hastening of sexual maturity, improving sperm quality, increasing fertility and better development of embryos. It is considered as one of the essential feed additive in combating the adverse effect of climate change on production performance of animals. This review mainly focuses on source, structure and use of astaxanthin as an antioxidant, anti-inflammatory, immune stimulator and for improving productive performance of bovines.